PEMUKIMAN PENDERITA KUSTA DAN FASILITASNYA DI DESA LAU SIMOMO, KABUPATEN TANAH KARO - Deni Sutrisna (Berkala Arkeologi Sangkhakala, 2006)
Settlement in Lau Simomo, Tanah Karo described the human historyregarding the residential area for lepers. The building of this areasupported the lepers in order to get a reasonably comfortable life. Theother facilities which part of the important things for treatment ofleprosy or character building are hospital and church.